BARTHES' SEMIOTICS ANALYSIS OF THE IMPLEMENTATION OF THE MEANING OF THE WORSHIP BY TAKMIR PURWOKERTO MOSQUE - Harisman, Harisman (HUNAFA Jurnal Studia Islamika, 2023)
The objective of this study is investigate the meaning of the worsahip practiced by Takmir Purwokerto Mosques through the use of Barthes’ semiotic analysis. It is argued that humans’ language goes dynamically in which the developments and changes in human language can cause a shift in meaning. To understand the phenomenon, this study used qualitaive research method. Data was colected through direct observation of worship activites and we also conducted in-depth interview with the participants. At the analysis stage, the author uses Barthes semiotics to reveal the implementation of the meaning of worship by the takmir of the Purwokerto mosque. The results of this study show that the importance of worship at the time of the Apostle has a broader sense. In this case, the implementation of the meaning of the term worship by the Takmir of the mosque in Purwokerto was only for mahdhah worship only. Mosques are not used for other activities as support for mahdhah worship. So the mosque is closed at certain times. Future studies need to focus on the reason why the moques is not open all the time as suggested by Islam.